„Stoisz prosty albo cię prostują”. Psychosomatyczne podstawy racjonalistycznych praktyk stoickich - Mazur, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The essay discusses popular rationalistic interpretation of stoic spiritual practices as rational control over nonrational aspects of human life. On the course of analyzing ancient stoics texts and recommendations concerning a good life the essay proves that the word “controlling” is not really proper translation of stoic intentions. Much better picture is of reason that takes care of condition of body and soul, or of reason that follows body and soul. Stoic reason is a tool for understanding and nursing nod controlling. Thus the ideal for stoic life is not reason but harmony, which is the best way of translating ancient Greek word tonos.